2013
DOI: 10.5430/jnep.v4n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Pregraduation clinical training program improves clinical competence of nurse students in Taiwan: An interventional study

Abstract: Background: Recruiting and retaining new graduate nurses are high priorities for hospitals confronting nurse vacancy issues. However, new graduate nurses may not meet the professional entry-level expectations in providing safe patientcare skills. The purposes of this study were to evaluate the effectiveness of a nurse pregraduation clinical training program by measuring students' clinical competency levels, from the students' and the preceptors' perspectives, and by analyzing students' decision to continue wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Considering the need for healthcare professionals to have both academic knowledge and practical skills, it is especially important for their training to integrate both of these elements. This need for effective training applies to both pre-employment training as well as continuing education [36, 37]. As the attention being paid to quality of care and practitioner competency increases, the need for tools to evaluate these competencies is growing.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the need for healthcare professionals to have both academic knowledge and practical skills, it is especially important for their training to integrate both of these elements. This need for effective training applies to both pre-employment training as well as continuing education [36, 37]. As the attention being paid to quality of care and practitioner competency increases, the need for tools to evaluate these competencies is growing.…”
Section: Discussionmentioning
confidence: 99%
“…The nursing literature continues to raise the concern regarding both the retention of the knowledge and skills acquired by nursing students, and the standard of competency in clinical skills among the newly graduated nurses. [101112] According to studies, clinical competency of new graduates has been identified as an area with statistically significant deficiency in nursing education. [1314] There are several factors involved in this issue, the most important of which is the inadequacy of some of the clinical educators.…”
Section: Introductionmentioning
confidence: 99%
“…In the first theme “feeling competent on graduation” a range of clinical skills or procedures were identified in which new graduates did not ‘feel’ competent to perform (Adair et al [ 3 ]; Dlamini et al [ 4 ]; Liou et al [ 5 ]; Liou and Cheng [ 6 ]); both new graduates and senior nursing clinicians supported this perception. This led to the exploration of ‘core’ and ‘advanced’ skills and competency highlighted by Liou et al [ 5 ] however this lacks clarity and requires further research.…”
Section: Introductionmentioning
confidence: 99%
“…In the first theme “feeling competent on graduation” a range of clinical skills or procedures were identified in which new graduates did not ‘feel’ competent to perform (Adair et al [ 3 ]; Dlamini et al [ 4 ]; Liou et al [ 5 ]; Liou and Cheng [ 6 ]); both new graduates and senior nursing clinicians supported this perception. This led to the exploration of ‘core’ and ‘advanced’ skills and competency highlighted by Liou et al [ 5 ] however this lacks clarity and requires further research. Students express the need for more practice within their programmes of study, even in the UK where the students spend 2300 h in a variety of settings – they still lack confidence (Bradshaw and Merriman [ 7 ], Farrand et al [ 8 ], Ross & Clifford [ 9 ], Dolan [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%